Association between economic growth and early childhood undernutrition: evidence from 121 Demographic and Health Surveys from 36 low-income and middle-income countries - Prof. Sebastian Vollmer, PhD; Kenneth Harttgen, PhD; Malavika A Subramanyam, DSc; Jocelyn Finlay, PhD; Prof. Stephan Klasen, PhD; Prof. S V Subramanian, PhD (Elsevier, 2014)
Background: Economic growth is widely regarded as a necessary, and often sufficient, condition for the improvement of population health. We aimed to assess whether macroeconomic growth was associated with reductions in early childhood undernutrition in low-income and middle-income countries. Methods: We analysed data from 121 Demographic and Health Surveys from 36 countries done between Jan 1, 1990, and Dec 31, 2011. The sample consisted of nationally representative cross-sectional surveys of children aged 0-35 months, and the outcome variables were stunting, underweight, and wasting. The main independent variable was per-head gross domestic product (GDP) in constant prices and adjusted for purchasing power parity. We used logistic regression models to estimate the association between changes in per-head GDP and changes in child undernutrition outcomes. Models were adjusted for country fixed effects, survey-year fixed effects, clustering, and demographic and socioeconomic covariates for the child, mother, and household. Findings: Sample sizes were 462 854 for stunting, 485 152 for underweight, and 459 538 for wasting. Overall, 35·6% (95% CI 35·4-35·9) of young children were stunted (ranging from 8·7% [7·6-9·7] in Jordan to 51·1% [49·1-53·1] in Niger), 22·7% (22·5-22·9) were underweight (ranging from 1·8% [1·3-2·3] in Jordan to 41·7% [41·1-42·3] in India), and 12·8% (12·6-12·9) were wasted (ranging from 1·2% [0·6-1·8] in Peru to 28·8% [27·5-30·0] in Burkina Faso). At the country level, no association was seen between average changes in the prevalence of child undernutrition outcomes and average growth of per-head GDP. In models adjusted only for country and survey-year fixed effects, a 5% increase in per-head GDP was associated with an odds ratio (OR) of 0·993 (95% CI 0·989-0·995) for stunting, 0·986 (0·982-0·990) for underweight, and 0·984 (0·981-0·986) for wasting. ORs after adjustment for the full set of covariates were 0·996 (0·993-1·000) for stunting, 0·989 (0·985-0·992) for underweight, and 0·983 (0·979-0·986) for wasting. These findings were consistent across various subsamples and for alternative variable specifications. Notably, no association was seen between per-head GDP and undernutrition in young children from the poorest household wealth quintile. ORs for the poorest wealth quintile were 0·997 (0·990-1·004) for stunting, 0·999 (0·991-1·008) for underweight, and 0·991 (0·978-1·004) for wasting. Interpretation: A quantitatively very small to null association was seen between increases in per-head GDP and reductions in early childhood undernutrition, emphasising the need for direct health investments to improve the nutritional status of children in low-income and middle-income countries. Funding: None.